PTU-089 Infliximab Down-regulates Stat 1, Alk And P44/42 Mapk Activation In Crohn's Disease Biopsies Cultured ex Vivo. (9th June 2014) - Bell, IM; Giuffrida, P; Biancheri, P; Ammoscato, F; Macdonald, T
Abstract : Introduction: Crohn's disease (CD) and ulcerative colitis (UC), the two main forms of inflammatory bowel disease, are characterised by increased mucosal activation of pro-inflammatory signalling molecules. The anti-tumour necrosis (TNF)-alpha monoclonal antibody infliximab is more effective in the treatment of CD than UC but its mechanism of action is still unknown. We therefore evaluated the effect of infliximab on the expression of a panel of phospho-proteins by inflamed CD and UC colonic biopsies cultured ex vivo . Methods: Colonic biopsies were obtained from macroscopically inflamed areas of 5 patients with CD and 2 patients with UC, and were then cultured for 24 h in 300ul of serum-free HL-1 medium with infliximab (5ug/ml), or control IgG1 (5ug/ml). The biopsies were then snap frozen and later lysed to extract the protein. A Path Scan RTK signalling array kit from New England Biolabs was used to measure the expression of a panel of 39 phosphorylated proteins in the biopsy homogenates. Results: Infliximab significantly reduced the expression of phosphorylated ALK, FLT3, EphB3, p44/42 MAPK, S6 Ribosomal Protein and Stat1 by over 40 fold compared to IgG1 in Crohn's disease biopsies cultured ex vivo . In UC biopsies infliximab did not induce any significant change in phosphoprotein expression compared to IgG1 control except for a 10 fold reduction in phospho-VEGFR2. Conclusion: Infliximab reduces the expression phospho-proteins Stat 1, ALK and p44/42 MAPK, which have a central role in sustaining the pro-inflammatory immune response. Differences in the effect of infliximab on the phosphorylation status of mucosal proteins may account for its different efficacy profile in CD and UC. Disclosure of Interest: None Declared.